The Effectiveness of the Kamsel Unit Role Through Dikmas Lantas to Reduce Traffic Accidents in Batang Resort Police - Manurung, Ruth Uliarta (Indonesian Journal of Police Studies, 2024)
The number of traffic accidents at the Batang Police Station has increased significantly over the last three years. Even though the level of security and safety of road users is the responsibility of the Kamsel Unit. Dikmas Lantas that have been running have also increased in frequency. This proves that the error lies not in quantity but in the quality of the Kamsel Unit role. This study intends to prove whether Dikmas Lantas affect traffic accident rates. The purpose of this research is to formulate problem-solving steps that can increase the effectiveness of the Kamsel Unit role through Dikmas Lantas. The research was analyzed using management theory, SWOT theory, effectiveness theory, and the concept of Dikmas Lantas. The research method used in this study is mixed methods. A mixed method is a combination of research methods between qualitative and quantitative. Research data comes from primary data, secondary data, and tertiary data. Primary data in the form of field observations and interview results; secondary data in the form of data, administration, and documents; and tertiary data in the form of literature studies of published scientific journals and theses. The research was conducted at the Batang Resort Police. The results of the study show that there is still no effect of Dikmas Lantas on the number of traffic accidents. The role of the Kamsel Unit through Dikmas Lantas is still not running effectively. The effectiveness of the Kamsel Unit’s role is influenced by internal factors and external factors. In addition, mistakes in determining activity targets at the planning stage also greatly affect the output from the implementation of Dikmas Lantas. The output is to reduce the number of traffic accidents. Based on the results of the research, a recommendation that can be made to achieve the role of the Kamsel Unit through more effective Dikmas Lantas is to make the anatomical mode of traffic accidents the target of Dikmas Lantas. In addition, there are some things can help the Kamsel Unit in carrying out Dikmas Lantas, that are improving coordination with internal and external parties, building good relations with the community, creating innovations related to Dikmas Lantas, use of social media and official vehicles as facilities and infrastructure.